The Political Lampoons in the Satirical Poems of Seyyed Heidar Helli - haydar zohrab; محمود خورسندي; Shaker Amery (دراسات في اللغة العربيّة وآدابها)
Arabic literature has long been blessed with a kind of poetry called lampoon in which the poet portrays ugly characteristics of an individual or a group. Gradually, the scope of this kind of poetry has been drawn to political literature, as in the works by the poets of the Umayyad Party, such as Akhtal and Meskin Daremi, and Ahwas, as well as Shiite poets. Some examples of this kind of poems can also be found in the poems of such poets as Komeit bin Zaid Asadi, Seyed Ismail Hemyari, and Da'bal Khazaee. This paper uses a descriptive method based on statistical data to study this kind of poetry in the satirical poems of Seyed Heidar Helli and seeks to introduce the various political lampoons used in this kind of poetry. It also tries to answer the question of why the poet is more inclined to use the "history-based lampoons" either directly or implicitly. The results of this study suggest that the political lampoons used in these satirical poem, either the direct or the indirect ones, can be divided into three categories: 1. Exaggerated lampoons, 2. lampoons laced with praise, and 3. History-based lampoons, the reason for the poet's desire to prefer the third category being its persuasive function because of its resort to historical data as well as the harmony of this type of lampoons to ethical and religious principles.